Rock And Roll Will Save Your Life : A Book By And For The Fanatics Among Us - Almond, Steve (New York Random House, 2010)
Rock and Roll Will Save Your Life" traces Almond's passion for "rawk" from his earliest (and most wretched) rock criticism to his eventual discovery of a music-crazed soul mate and their subsequent production of two little superfans. Along the way, Almond reflects on the delusional power of songs, the awkward mating habits of drooling fanatics, and why Depression Songs actually make us feel so much better.
Keywords: Popular Music History And Criticism; Biographies